Strategi Pengembangan Destinasi Pariwisata di Kepulauan Togean Provinsi Sulawesi Tengah - Badarab, Fitriah; Trihayuningtyas, Endah; Suryadana, M. Liga (Universitas Pendidikan Indonesia, 2017)
This research aims to know the strategy of development of Tourism Destinations in the Togian Islands, Regency Tojo Una-Una, Central Sulawesi Province. The island has become a major national tourist's destination in Indonesia between 50 regions in Indonesia. However, the number of tourists visited the island were fluctuated for the last three years. This research examined the tourism strategy formulation based on internal and external factor analysis at the destination. The research used some instruments to compile data, such as observation, interview, questionnaires, and documentation. The research result indicated that there were several strategies that could be implemented in developing the Togian island. The strategies were as follows: 1) developing cultural and natural tours, such as bird watching, beach activities and Bajeu village visits; 2) establishing close relationship and cooperation between public and private sectors; 3) attracting foreign investors; 4) building and maintaining the tourist facilities in some strategic locations; 5) increasing community awareness for developing tourism; 6) developing ethnic-based tour packages. Therefore, some recommendations for the destination are on developing cultural, natural, and culinary tourism; improving the public facilities; developing accessibility; and strengthening cooperation among stakeholders.